Development of an Evaluation Indicator System for Medium–Low Yield Farmlands on the Basis of the Synergistic Improvement of Soil Carbon Sequestration and Production Capacity: A Theoretical Framework - Hongbin Liu; Hebin Zhang; Shuai Wang (Agronomy)
This study aims to systematically examine the concept and characteristics of medium–low yield farmland (MLYF), to identify the key factors influencing the coordination between soil carbon sequestration (SCS) and production capacity (PC) in MLYF, and develop an evaluation indicator system (EIS) to provide innovative approaches for transforming MLYF to enhance food security and emission reduction capabilities. Focusing on the synergistic improvement of SCS and PC in MLYF, this research employs theoretical analysis, systematic inference, and inductive deduction to analyze the relationships between these factors and construct the EIS. The findings reveal that (1) MLYF is characterized by inherent limitations and suboptimal management practices, resulting in low grain PC but significant potential for yield improvement. (2) A positive correlation exists between the soil organic carbon (SOC) content and crop yield, with MLYF demonstrating substantially greater potential for synergistic improvement than high-yield fields. (3) On the basis of soil science principles, the key factors affecting the synergistic enhancement of carbon sequestration and productivity in MLYF include climatic conditions, soil properties, and biological factors. (4) A comprehensive “Demand-Function-Dimension-Element-Indicator” framework was established, incorporating an EIS designed for national, provincial, and city/county levels to address the management requirements of MLYF across various scales, thereby facilitating comprehensive quality improvement. This research contributes to the theoretical understanding of MLYF transformation, offering valuable insights for ensuring national food security and achieving carbon emission reduction goals.